PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN SELF EFFICACY, DESENTRALISASI, DAN BUDAYA ORGANISASI SEBAGAI VARIABEL PEMODERASI - Yanti, Putu Medha; Suardana, Ketut Alit (E-Jurnal Akuntansi, 2015)
The purpose of a company can be realized if there is capability of professional managers. One of the tools used to assess the performance is to look at the level of the liveliness of the managers or budget participation of employees. The aim of this research is to determine the effect of budgeting participation on managerial performance with self efficacy, decentralization, and organizational culture as the moderating. Object of the research has done at BPR in Denpasar city for fiscal year 2014, by purposive sampling method and  moderate regression analysis. The results showed negative effect of budgeting participation on managerial performance and self efficacy, decentralization, and organizational culture increase our relationships.
Keywords: budgeting participation, managerial performance